A SURVEY ON THE ORAL SOURCES OF THE NARRATION OF DELİ DUMRUL AND ITS DİYARBAKIR VARIANT - Şimşek, Esma (TÜRKİYE TEMEL BİLİMLER ARAŞTIRMA VAKFI, 2020)
Dede Korkut Stories, which have an important place in Turkish culture, continues to exist in oral sources as well as in written sources. Today, in Turkish world, it is possible to come across tale version of stories -though not all of them- such as Bamsı Beyrek, Tepegöz and Deli Dumrul. Among these, 16 variants of the Deli Dumrul Story, which is our study subject, have been determined to be told among the people. Although Muharrem Ergin said in the past that the story had one narration, this number has increased considerably over time. As a matter of fact, while Tuncer Gülensoy stated that it was also told in a Turkish town close to the Skopje region, the capital of Macedonia, in the narrative called “Ecel” (The Game of Azrail)”, which is told in Elazığ, it is the version of the mentioned story that took a bit the form of tale and a bit Islamic color. In addition; it has also been determined that it has been told in different regions with the names such as “The Tale of Azrail”, “The Child Who Served Azrail for Seven Years”, “Azrail and the Hunter”, “Azrail and the Man”, “A Forty-Year Life Granted by God”, “Bolvadin Narration of Deli Dumrul” and “Makav (Deli)”. The narration of the same story under the name “Elo Dîno” in Cizre is very important for the formation of cultural unity. Also, a variant of the Deli Dumrul Story which is told in a wide range of area from east to west, from south to north depending on the dialect features of the region, is compiled from Hayat Özmen, who is living in Silvan district of Diyarbakır. The story has moved far from its origin, and has become a tale like its other variants. In this article, this story, which is told completely in tale version, will be compared with the story of “Duha Kocaoğlu Deli Dumrul,” which takes place in Dede Korkut Stories, will be examined in various aspects and will be evaluated symbolically.

Türk kültüründe önemli bir yere sahip olan Dede Korkut Hikâyeleri, yazılı kaynakların yanı sıra sözlü kaynaklar içerisinde de varlığını sürdürmektedir. Bugün, Türk dünyasında, -hepsinin olmasa da- Bamsı Beyrek, Tepegöz ve Deli Dumrul gibi hikâyelerin masallaşmış şekline rastlamak mümkündür. Bunlar içerisinde, çalışma konumuz olan Deli Dumrul Hikâyesinin, halk arasında anlatılan 16 varyantı tespit edilmiştir. Geçmişte Muharrem Ergin, hikâyenin tek rivayetinin olduğunu söylese de zamanla bu sayı epeyce artmıştır. Nitekim Tuncer Gülensoy, Makedonya’nın başkenti olan Üsküp bölgesine yakın bir Türk kasabasında da anlatıldığını belirtirken Elazığ’da anlatılan “Ecel (Azrail’in Oyunu)” adlı anlatı da, adı geçen hikâyenin biraz masallaşmış biraz da İslami renge bürünmüş şeklidir. Ayrıca; “Azrail Masalı”, “Azrail’e Yedi Yıl Hizmet Eden Çocuk”, “Azrail ile Avcı”, “Azrail ve Adam”, “Tanrı Tarafından Bağışlanan Kırk Yıllık Hayat”, “Deli Dumrul’un Bolvadin Rivayeti” ve “Makav (Deli)” gibi adlarla değişik bölgelerde anlatıldığı da tespit edilmiştir. Aynı hikâyenin Cizre’de “Elo Dîno” adıyla anlatılması kültürel birliğin oluşumu açısından oldukça önemlidir. İşte, doğudan batıya, güneyden kuzeye geniş bir alanda bölge ağız özelliklerine bağlı olarak anlatılan Deli Dumrul Hikâyesinin bir varyantı da Diyarbakır’ın Silvan ilçesinde yaşayan Hayat Özmen’den derlenmiştir. Hikâye, aslından bir hayli uzaklaşmış olup, diğer varyantları gibi masallaşmıştır. Bu yazıda, tamamen masallaşmış bir şekilde anlatılan bu hikâye, Dede Korkut Hikâyeleri içerisinde yer alan; “Duha Koca Oğlu Deli Dumrul” hikâyesi ile karşılaştırılarak çeşitli yönleriyle incelenecek ve sembolik açıdan değerlendirilecektir.
DELİ DUMRUL HİKÂYESİNİN SÖZLÜ KAYNAKLARI VE DİYARBAKIR VARYANTI ÜZERİNE BİR İNCELEME
Keywords: Cultural Studies; Kültürel çalışmalar